Experimental acute anti-inflammatory activity of preparations with complexed cannabidiol in carriers - Daniel Ribeiro Grijó; Edvalkia Magna Teobaldo da Rocha; Vitor de Cinque Almeida; Ciomar Aparecida Bersani Amado; José Eduardo Olivo; Oswaldo Curty da Motta Lima (Universidade de São Paulo, 2023)
Abstract Cannabidiol (CBD) is a bioactive compound with promising anti-inflammatory results but has low aqueous solubility. Complexation of drugs with this characteristic in carriers is an alternative to improve their efficiency. This study aimed to prepare and characterize CBD complexes in different carriers, and to evaluate the anti-inflammatory effect of such preparations using an experimental model of edema induction in rat paws. The results were compared to a reference drug, ibuprofen (IBU). The carriers evaluated were beta cyclodextrin (bCD) and activated charcoal (AC). Quantification of the drugs in the complexes was determined, and different qualitative analyses were also performed. Oral treatments in single doses with CBD showed inhibitory effects similar to that of IBU, potentiating its bioactivity without significant adverse effects. CBD*bCD doses at 4.375, 8.75, 17.5, and 35 mg/kg significantly reduced the intensity of edema compared to equivalent doses of pure bioactive. In contrast, CBD*AC did not generate benefits. There was no significant inhibitory effect on myeloperoxidase activity, requiring more specific analyses to assess this parameter. The results suggest that the CBD*bCD complexation is perfectly feasible, increasing its anti-edematogenic efficacy in the experimental model used.